Pancreatic Metastasis from a Solitary Fibrous Tumor of the Central Nervous System - Osuga, Takahiro; Hayashi, Tsuyoshi; Ishiwatari, Hirotoshi; Ono, Michihiro; Yoshida, Makoto; Kimura, Yasutoshi; Hasegawa, Tadashi; Sato, Yasushi; Sato, Tsutomu; Miyanishi, Koji; Takimoto, Rishu; Kobune, Masayoshi; et al. (JOP. Journal of the Pancreas, 2014)
Context Solitary fibrous tumor of the central nervous system is uncommon, with only around 200 reported cases. Further, extracranial metastasis is extremely rare, and only 5 cases of hematogenous metastases have been reported so far. To the best of our knowledge, there have been no reports of solitary fibrous tumor of the central nervous system metastasizing to the pancreas. Case report A 62-year-old woman was referred for evaluation of a pancreatic mass, which was strongly suspected to be a neuroendocrine tumor. However, the histological findings and immunohistochemical profile indicated the presence of a solitary fibrous tumor. Because the medical history revealed previous transcranial resection for intracranial meningioma 16 years ago, we conducted a pathological review of the brain specimen obtained by the first operation and found that it had the same histology and immunohistochemical profile as the current endoscopic ultrasound-guided fine-needle aspiration specimen. Consequently, the final diagnosis, on the basis of the brain specimen, was changed from meningioma to solitary fibrous tumor of the central nervous system, and the pancreatic mass was diagnosed as metastasis from solitary fibrous tumor of the central nervous system. The patient underwent middle pancreatectomy; the pancreatic specimen also had the same histology and immunohistochemical profile as the brain specimen. Conclusion Histological findings and immunohistochemical profile obtained by EUS-FNA are invaluable for the correct diagnosis to avoid excessive surgical procedures. Image: Middle pancreatectomy specimen.